Atmospheric Reactivity of Methoxyphenols: A Review - Liu, Changgeng; Chen, Dandan; Chen, Xiao’e (Environmental science & technology, 2022)
Methoxyphenols emitted from lignin pyrolysis are widely used as potential tracers for biomass burning, especially for wood burning. In the past ten years, their atmospheric reactivity has attracted increasing attention from the academic community. Thus, this work provides an extensive review of the atmospheric reactivity of methoxyphenols, including their gas-phase, particle-phase, and aqueous-phase reactions, as well as secondary organic aerosol (SOA) formation. Emphasis was placed on kinetics, mechanisms, and SOA formation. The reactions of methoxyphenols with OH and NO3 radicals were the predominant degradation pathways, which also had significant SOA formation potentials. The reaction mechanism of methoxyphenols with O3 is the cycloaddition of O3 to the benzene ring or unsaturated CC bond, while H-abstraction and radical adduct formation are the main degradation channels of methoxyphenols by OH and NO3 radicals. Based on the published studies, knowledge gaps were pointed out. Future studies including experimental simulations and theoretical calculations of other representative kinds of methoxyphenols should be systematically carried out under complex pollution conditions. In addition, the ecotoxicity of their degradation products and their contribution to SOA formation from the atmospheric aging of biomass-burning plumes should be seriously assessed.